Effects of pressure gradients on entropy generation in the viscous layers of turbulent wall flows - McEligot, D; Nolan, K; Walsh, E; Laurien, E (2008)
By employing results of direct numerical simulations, it is possible to examine entropy generation due to friction in the viscous layers of turbulent flows with significant streamwise pressure gradients, both for boundary layers and channels. About two-thirds or more of the entropy generation per unit surface area S″ occurs there. Increasing the pressure gradient increases direct dissipation and decreases turbulent dissipation (in wall coordinates). The integral of the entropy generation rate per unit surface area to the edge of the viscous layer is relatively insensitive to pressure gradients for channels but decreases moderately for boundary layers. © 2007.